Analisis Pengaruh Organizational Capital terhadap Tingkat Penghindaran Pajak Perusahaan Pertambangan yang Terdaftar di Bursa Efek Indonesia - Tri Prastyo, Slamet; Nuryanah, Siti (Prodi Akuntansi UIN Sunan Ampel Surabaya, 2024)
This study aims to analyze the effect of organizational capital on corporate tax avoidance. The population of this study are mining companies listed on the Indonesia Stock Exchange in the 2012-2021 periods. Using panel data regression with the common effect model, the results of the study found that organizational capital has a negative and significant effect on corporate tax payments. In other words, high organizational capital can increase corporate tax avoidance. Companies that are able to manage organizational capital properly will be able to create organizational efficiency, one of which is through tax management that the company will choose. This study confirms previous findings that organizational capital creates organizational innovation and organizational learning abilities in related to tax avoidance. This study also strengthens the previous findings that companies with high organizational capital have a greater chance of tax avoidance. The research has implications for the company's internal policy as a taxpayer to increase its organizational capital so that it can have an effective management. On the other hand, the tax authorities can make policies that support the creation of compliant taxpayers and ethical corporate tax management.